Implementation of Evidence-Based Nursing for Expelling Sputum in Tuberculosis Patients with Chest Physiotherapy and Effective Coughing Exercises: A Case Study - David Richard, Selvia; Ariyanto, Heri; Setiawan, Henri (Alta Dharma Publisher, 2022)
Tuberculosis is a bacterial infection caused by the bacillus Myobacterium tuberculosis. is an aerobic bacterium in the form of a rod bacillus, but this bacterium survives against acid, the manifestations that appear are usually the patient complains of coughing up phlegm. Non-pharmacological techniques that can be used to remove phlegm are to perform chest physiotherapy and teach effective coughing, this technique is still rarely used in the field. Nurses are more likely to collaborate in giving antibiotics. This case study was conducted to present the implementation of evidence based nursing providing effective chest physiotherapy and coughing exercise as an effort to expel phlegm in tuberculosis patients. Physical examination was carried out by the persistent method in tuberculosis patients. Indonesian Nursing Diagnosis Standards (IDHS), Indonesian Nursing Outcomes Standards (SLKI), Indonesian Nursing Intervention Standards (SIKI). The nursing diagnosis of ineffective airway clearance with the diagnosis number 0001 was given nursing interventions in the form of chest physiotherapy and effective coughing. After being given nursing intervention for 3 days, the ineffective airway clearance was resolved with a patent airway which was characterized by normal breathing frequency, regular breathing rhythm, no additional breath sounds, the patient was able to expel sputum. Effective chest and cough physiotherapy is considered effective in overcoming the problem of airway clearance.